SOCIAL LITERACY PRACTICES IN SUPERVISED INTERNSHIP - de Souza Esmeraldo, Moema; Rolim de Lima, Neivana; Freitas de Alencar, Datyane (Revista Gênero e Interdisciplinaridade, 2026)
This article aims to discuss possibilities for literacy through didactic-methodological knowledge of Portuguese language and literature teaching in the final years of elementary school and high school, taking as a starting point for reflection on literary literacy as a pedagogical possibility in supervised internships. Initially, a documentary analysis of the main legislation regulating supervised internships as mandatory in teacher training in Brazil is carried out (MEC, 2002; 2019; 2008; 2015; 2024). Following this, a review of different conceptions of literacy is developed, according to Soares (2001), Street (2014a, 2014b), Castanheiras (2014), Esmeraldo (2022, 2024) and Cosson (2018). Finally, the results of the investigation into literary literacy as an effective possibility for the realization of the social practice of literary reading in the classroom are presented, highlighting methodologies for working with literary reading as the focus of the social practice of literacy in the supervised internship